Personal hygiene and asymptomatic bacteriuria in women aged 40 to 65 years - Ambarwati, Farasita; Elfani, Maysarah; Margastutie, Apriani; Dahuri, Nurul Mahirah Binti Mohd. (Universa Medicina, 2011)
Asymptomatic bacteriuria (ABU) is one of the bacterial infections most frequently found in women in all age groups, particularly in postmenopausal women. Around 10-25% of women suffer from symptomatic urinary tract infection (UTI) all their life. Several risk factors are associated with the occurrence of ABU in females, such as a history of UTI, sexual activity, diabetes mellitus, personal hygiene, sexual hygiene, and menopausal status. The aim of this study was to determine the most important risk factor of influence on ABU in premenopausal and postmenopausal women at the Pasar Minggu Primary Health Center. This was an analytical cross-sectional observational study. The study sample consisted of premenopausal and postmenopausal women aged 40-65 years visiting a Primary Health Center of the Pasar Minggu Subdistrict, South Jakarta, who were selected by consecutive sampling. The data analysis used prevalence ratios and logistic regression. The results of the study showed that the prevalence of positive bacteriuria in females was 45%. Sexual activity, sexual hygiene, menopausal status of the females, and personal hygiene were risk factors of ABU. Personal hygiene was the most influential risk factor on the occurrence of ABU in both premenopausal and postmenopausal women. Since in this study ABU was present in 45% of women, thus making it a common disorder in middle-aged and older women, it is recommended that the primary care physician directly administer therapy to women with symptoms of UTI without performing laboratory analysis.